2020
DOI: 10.3332/ecancer.2020.1110
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and haematology services in a cancer centre from a middle-income country: adapting service delivery, balancing the known and unknown during the pandemic

Abstract: The COVID-19 pandemic has caused major disruptions in multiple spheres of healthcare delivery in the world. Developing nations have had to tackle this unanticipated crisis in the midst of various other healthcare delivery issues and resource constraints. As a tertiary level cancer care provider located in an eastern Indian city, a COVID-19 hotspot, we share our experience from the perspective of haematology and haematopoietic stem cell transplantation (HSCT) services. The primary challenges related to infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…We identified ongoing concerns as states remain under restrictions and as the U.S. begins to emerge from the pandemic. In terms of practice changes, similar to our findings, other studies have also reported delays to cancer treatment for older adults [ 14 , 19 ] and appointments for cardio-oncology [ 20 ], as well as for treatment of hematological malignancies in one middle-income country [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…We identified ongoing concerns as states remain under restrictions and as the U.S. begins to emerge from the pandemic. In terms of practice changes, similar to our findings, other studies have also reported delays to cancer treatment for older adults [ 14 , 19 ] and appointments for cardio-oncology [ 20 ], as well as for treatment of hematological malignancies in one middle-income country [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…The COVID-19 pandemic is an unprecedented global crisis that impacted pediatric cancer health care systems worldwide, with a greater effect on low and middle-income countries (LMIC). 2,3,12,[15][16][17] One year into the pandemic, the initial fears and concerns have evolved along with treatment and prevention strategies for COVID-19 and multiple effective vaccines have been developed in record time. As the pandemic continues to unfold, our 4 surveys performed over the first year of the pandemic in Latin America show the mediumterm effects on the care of pediatric cancer patients; and reveal how the medical systems and medical professionals adapted to the different health care crises that originated from the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…1 One year into the pandemic, multiple measures were implemented by governments attempting to slow the spread of COVID-19 and to ameliorate the burden on their medical systems. 2,3 These included home isolations, closing borders, schools, nonessential business, and restricting travel within and between countries. The fear generated by the pandemic resulted in patients being unable or unwilling to seek medical care.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic is an unprecedented global crisis that impacted pediatric cancer healthcare systems worldwide, with a greater effect on low-and middle-income countries (LMIC). 2,3,12,[15][16][17] One year into the pandemic, the initial fears and concerns have evolved Therefore, the answers to our surveys reflect cautionary adaptation, as most medical systems organized to face unpredictable healthcare delivery crises. Not surprisingly, higher levels of treatment disruptions were reported in countries with HCE below 7%, and in countries with higher national burden of COVID-19, reflected by a higher incidence rate and case fatality rate above 2%.…”
Section: Discussionmentioning
confidence: 99%
“…Severe acute respiratory virus (SARS‐CoV‐2) outbreak resulting in coronavirus 2019 disease (COVID‐19) caused an unprecedented pandemic that led to more than 400 million cases and close to 6 million deaths around the world (date March 7, 2022) 1 . More than 1 year into the pandemic, multiple measures were implemented by governments attempting to slow the spread of COVID‐19 and to ameliorate the burden on their medical systems 2,3 . These included home isolations, closing borders, schools, nonessential business, the use of personal protective equipment (PPE), and restricting travel within and between countries.…”
Section: Introductionmentioning
confidence: 99%